Analysis of the role played by networks in the processes of French SMEs’internationalization in West Africa. - (:unkn) unknown (My University, 2023)
The international support of French SMEs by institutional networks such as Business France, BPI France and CCIs (Chambers of Commerce and Industry), although significant, is the subject of little attention in research work. This article seeks to explore their functioning and their contribution to the internationalization of French SMEs in West Africa. Thus, a mixed qualitative methodology consisting of conducting semi-structured interviews with 11 public internationalization agents and the study of four SMEs that export to West Africa was used. The results reveal an abundance of resources provided by institutional networks for a possible acceleration of the internationalization process of SMEs that already have international experience using their own networks. This choice raises the question of the opportune moment to solicit institutional networks. A first theoretical contribution calls into question the theories, which postulate that the SME does not have an international experience and first solicits institutional networks before freeing itself from them after gaining experience. A second contribution remains the hybridization of institutional, social and private networks.
Keywords: African Research